Contamination of Japanese foodstuffs of terrestrial origin after the Fukushima nuclear accident and related dose assessment: Part 2: ingestion dose assessments for the first year after the accident. Issue 1 (14th February 2014) - Renaud, Ph.; Simon-Cornu, M.; Gonze, M.-A.; Mourlon, C.; Parache, V.; Korsakissok, I.; Navarro, E.; Cessac, B.; Rannou, A.; Champion, D.
Abstract : This article proposes an assessment of the ingestion doses potentially received by people living in the Japanese areas most severely affected by the radioactive deposits due to the Fukushima nuclear accident. The assessment distinguishes two consecutive periods: the first 2 months (March 15th to May 15th 2011) and the rest of the year 2011, according to the two main foodstuff contamination periods identified (Renaud et al., 2013). On the basis of the worst-case hypothesis that can reasonably be made, the estimated doses are much lower than they might have been in other circumstances, on account of generally moderate levels of contamination for most foods, early evacuation of the most severely affected areas and the consumption bans ordered by the Japanese authorities. Thus, a single ingestion of 100 g of leafy vegetables in the early days by a one-year-old child living in non-evacuated localities near Iitate and Kawamata could have led to an equivalent dose to the thyroid of about 25 mSv; and to a thyroid dose of about 140 mSv for the rather unrealistic scenario of a daily consumption. Because of the rapid decrease in the contamination of vegetables and a much weaker contamination of other crops, and thanks to measures taken by the authorities (prohibition of consumption, use of certain fodder, etc.), the ingestion doses potentially received during the remainder of the year 2011 are estimated to be below 1 mSv. In the event that sales limits would have been ignored, only repeated consumption of mushrooms would have led to doses above that level. Even with the worst-case hypotheses, the doses potentially caused by ingestion are much lower than those resulting from outdoor exposure to radioactive deposits: approximately several millisieverts in a year for the population living in the non-evacuated localities near Iitate and Kawamata.